(untitled) (Global Journal of Science Frontier Research, 2014)
A longitudinal study was carried out to determine the prevalence and incidence of mastitis in lactating dairy cows from November 10, 2011 to June 25, 2012 in six purposively selected smallholder dairy farms in Hawassa and Wendo-Genet districts, Ethiopia. The study was carried out through field screening surveys by California mastitis test for each quarter milk sample, followed by retesting negatives group for mastitis twice a month during the study period to estimate the incidence of mastitis. At the time bacteriological examinations to identify the causative agents from mastitis positive cows were carried out. A total of 122 milking cows were examined, out of which 77 (63.1%) and 152 (31.1%) were found positive for mastitis on the basis of California mastitis test at cow and quarter level, respectively. Out of the total quarters examined, 25 (5.12%) were recorded as a blind teats. The incidences of mastitis were seen to be 0.49 in three month study period. Slight variations in incidence rate between different farms were revealed. Higher incidence rate of 0.54 was recorded in cows kept in bad concrete in comparison to cows kept in good concrete which is 0.41. On the other hand, higher incidence rate was recorded in single and three or above parity; in early and late stage of lactation.